Determinants of Greenhouse Gas Emissions in the Transportation Sector in Indonesia: Official Statistics and Big Data Approach - Arisanti, Restu; Purnamawati, Suci; Muslim, Agus (International Journal of Energy Economics and Policy, 2024)
The Covid-19 pandemic has affected every aspect, including the greenhouse gas emissions from the transportation industry. The adoption of Lockdown during the Covid-19 outbreak has decreased greenhouse gas emissions in the transportation sector. Studying the variables that affect the transportation sector’s greenhouse gas emissions during the COVID-19 pandemic is particularly fascinating. Big data and official statistics were combined to create the data for this study. Official statistics are sourced from Statistics Indonesia (BPS) and the National Development Planning Agency (BAPPPENAS) while big data is sourced from the google mobility index. Based on the results of the generalized linear model with the gamma link, it can be concluded that the growth of GRDP per capita and the mobility of people to workplaces have a negative effect on greenhouse gas emissions in the transportation sector, mobility of the population to groceries and pharmacies has a positive effect on greenhouse gas emissions in the transportation sector, while people’s mobility to recreation and retail has no effect on greenhouse gas emissions in the transportation sector. During the Covid-19 pandemic, population mobility to Workplaces which showed reduced work from an office (WFO) and increased work from home (WFH) had the greatest influence on reducing greenhouse gas emissions in the transportation sector. Work from home (WFH) can be used as a solution to reduce greenhouse gas emissions in the transportation sector at the beginning of the Covid-19 endemic.